Hypermethylation of TUSC5 genes in breast cancer tissue - Bubnov, V.; Moskalev, E.; Petrovskiy, Y.; Bauer, A.; Hoheisel, J.; Zaporozhan, V. (Experimental Oncology, 2012)
Aim: Breast cancer (BC) is one of the most common forms of cancer amongst females. Early diagnosis, prognosis and therapy plays crucial role in the survival of patients with breast cancer. The study was aimed on identification of potential markers for early BC diagnostics by means of genome-wide comparative analysis of gene expression in cancer and normal tissue of breast. Methods: The analysis of gene expression in 15 invasive adenocarcinoma specimens and 15 normal breast tissue was conducted using the full-genome microarrays Sentrix HumanWD-6V3 BeadChip (Illumina). Methylation of TP53INK1 and TUSС5 promoters was interrogated by the combined bisulfite restriction analysis (COBRA). Results: Analysis of gene expression in the samples of breast adenocarcinoma revealed abnormal expression of more than 2,300 genes. While genes TFF1, S100P, ERBB2, TOP2A, CDF15, HOOK1, DNAJC12, CORO2A were up-regulated in cancer, decreased expression was found for genes TUSC5, SFRP1, PPPQR1B, NTRK4, TIMP4, BARD1, AKR1C2, TP53INK1 and others. Analysis of DNA methylation of TUSC5 by COBRA revealed higher levels of exon 1 methylation (11/12) in samples of breast cancer, whereas the gene was essentially unmethylated in matched normal appearing tissue of breast (2/12). TP53INK1 gene was methylated neither in cancer nor in normalcy. Conclusion: A total of 149 genes exhibited the highest difference in expression in cancer versus normal appearing tissue of breast. Most prominent down-regulated candidates, TUSC5 and TP53INK1, were reported for the first time in breast cancer and may be considered as potential markers of the disease. Aberrant DNA hypermethylation of TUSC5 suggests epigenetic mechanism of cancer associated down-regulation.